Diseño y construcción de un prototipo de cortadora y grabadora láser CNC para el Centro de Investigación I2TEC de la UNL. - Narváez Barragán, David Alejandro (2023)
This research work details the development of a prototype CNC laser engraver and cutter, capable of controlling movements automatically and coordinated in the two axes of the two-dimensional plane (X, Y) during the workflow. This prototype is an application of modern technologies focused on industry and manufacturing processes; which aims to contribute to the academic and research development within the projects of the I2TEC Research Center. The project consists of five stages for its development; it begins with a bibliographic review on machines - CNC tools and laser applications for manufacturing processes of cutting and engraving, which allows us to establish criteria and requirements necessary for the development of the prototype. In this way the hardware and software are selected among the common alternatives that are commercially available in the market, and then continue with the design process using 3D software; of each of the parts that make up the prototype. From the CAD design, the physical implementation of the prototype is made, and then proceed with the adjustment, calibration and functional testing of the implemented prototype. With this prototype is intended to show the importance of applied research, and at the same time promote the development of tools that help in teaching processes within the technical area and contribute to improve the academic research environment. Keywords: Prototype, Laser, Machine - tool, CNC, CAD, Two-dimensional, Manufacturing, 3D.